The comparison of the effects of post-activity performance enhancement on foot plantar pressure and vertical jump in traditional set and cluster set training configurations - Mehmet Kale; Abdurrahman Boyacı; Ali Berkay Tolalı; Yeliz Yol; Ezgi Ayaz; Murat Tutar; Umut Davut Başoğlu (Journal of Men's Health)
Background: There is no study about the effects of post-activity performance enhancement on foot plantar pressure and vertical jump in different set configurations. This study aimed to compare the effects of post-activity performance enhancement on foot plantar pressure and vertical jump in traditional set and cluster set training configurations. Methods: The study included 27 volunteer university students (age: 20.0 ± 1.2 year, height: 180.2 ± 6.9 cm, body weight: 76.0 ± 11.8 kg). Static foot plantar pressure (SFPP), countermovement jump (CMJ), and squat jump (SJ) were performed as pre-tests 8 min after the half-squat 1 repetition maximum (HS 1RM) test. After pre-tests, 12 reps of training were performed with 70% of the HS 1RM by varying the training configurations of 1 × 12 reps traditional set (TS) on the 4th day, 3 × 4 reps cluster set 1 (CS1) with 30 s rest on the 8th day, and 6 × 2 reps cluster set 2 (CS2) with 10 s rest on the 12th day. Post-tests were performed in the following of each configuration. Repeated Measures Analysis of Variance (ANOVA) was used for the statistical comparison of the tests in four different time intervals. Results: There were no statistically significant SFPP differences in four different time periods, while statistically significant differences were found in the CMJ (p < 0.001) and SJ (p = 0.002). Pairwise comparisons showed that CMJ pre-test (CMJPRE) had statistically significant differences with CMJTS, CMJCS1 and CMJCS2. There were also differences between SJPRE and SJCS1, SJTS and SJCS2 for the SJ (p < 0.05). Conclusions: In conclusion, based on the results of the study, it is recommended to use any of the TS, CS1 and CS2 configurations to increase CMJ and to use the CS1 configuration to increase SJ as a performance enhancement at 8 min post-activity.